The effect of microgravity model (hind limb suspension) on the levels of testosterone and LH in rats - Sh Ghayumi; A Khoshvaghti; A NurMohammadi (فصلنامه ابن سینا)
Background: Weightlessness has different effects on human physiology. Microgravity causes major changes in various body systems in space; like changes in function of sexual system and the secretion of hormones. This study aimed to evaluate the effect of microgravity on the levels of testosterone and LH in rats.